Multi level marketing of Avon Cosmetisc (M) Sdn Bhd / Siti Aisha Wahida Abdul Malik - Abdul Malik, Siti Aisha Wahida (2009)
The purpose of this report is to focus on the issue in multi level marketing. Lack of motivation among sales leader in order to encourage sales leader to work for Avon Sales Leadership framework is important in order to provide sales leader’s quality of work or all work in general will deteriorate. This report is conducted in lies of increasing competition and internal management that have brought challenges to the multi level company. Nowadays, customers are well informed, have better needs and wants and they have higher expectation regarding the product. The objectives of the report are to emphasis the motivation among sales leader in order to encourage them more productive and to ascertain the effectiveness of using internet marketing which is direct selling through online is more efficient. One of the purposes of this report is to enable Avon cosmetics (M) Sdn Bhd business expansion, while their distribution channels, thus making them close to end user. The lack of motivation among sales leader showed that Avon sales performance is in constantly level in Avon Sales Leadership Framework. Finally, recommendations are given to the management of Avon cosmetics (M) Sdn bhd for further improvements.